IbM Industri Kreatif (Sandal dan Sepatu Lucu) - Nevi Danila; Ali Lating (Jurnal ABM Mengabdi, 2017)
The development of creative industry which is a product of sandals and cute shoes is one of the efforts that has been declared by the government. People with their various ideas and creativity strive to get this business opportunity because the results can promise for the improvement of society. The partner industry in this creative is Mrs. May (mitra1) and Ibu Indayanik (partner 2). The first growing problem is: (1) Unfulfilled consumer demand for the resulting product, this is due to the use of tools used for sewing edges is still limited and requires a tent for the exhibition. The growing problem is its impact in the use of juki machines and embroidery machines. The solutions offered are: (a) for production aspect to the first partner will be provided: (1) sewing machine, so it can be utilized optimally; (2) Spon scissors to cut the mall that has been drawn with variation so that more neatly and its use more) Tents are used for activities at the time of the exhibition. While for the second partner (1) will be provided additional juki machine to facilitate the production process, (2) Sewing machine to sew from cute shoes and tents for the exhibition; (3) Tents are used for exhibition (b) for management aspect, both partners will be given: (1) Training in recording of simple financial report for SME. This activity is done so that the two partners can find out what the results are needed or what costs should be incurred, so later can be used for decision making. (2) Training on internet marketing and (3) internet marketing module development and financial report module for SMEs. The outcomes to be generated are (1) reports on the results of activities, which are the outputs that must be made by the implementing team as a form of grant responsibility and (2) scientific articles to be published in national journals and printed publications